Study on road accidents in pedestrians, cyclists and motorcyclists in the province of La Rioja - Argentina 2011-2015 - Andrada, Marcos Javier (2017)
Fil: Andrada, Marcos Javier. Universidad Nacional de La Rioja; Argentina.